2011
DOI: 10.1016/j.molcel.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Sirt3 Promotes the Urea Cycle and Fatty Acid Oxidation during Dietary Restriction

Abstract: In the above article, the author's name, Mark K. Devries, was spelled incorrectly. We regret any inconvenience this may have caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 0 publications
2
84
0
Order By: Relevance
“…Under fasting conditions, SIRT3-deficient mice show decreased fatty acid b-oxidation, resulting in elevated serum long-chain fatty acid levels (54,58). Inefficient fatty acid oxidation may contribute to the reduced ATP levels of SIRT3-deficient mice under fasting conditions (1).…”
Section: Sirt3 Promotes Fatty Acid Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Under fasting conditions, SIRT3-deficient mice show decreased fatty acid b-oxidation, resulting in elevated serum long-chain fatty acid levels (54,58). Inefficient fatty acid oxidation may contribute to the reduced ATP levels of SIRT3-deficient mice under fasting conditions (1).…”
Section: Sirt3 Promotes Fatty Acid Oxidationmentioning
confidence: 99%
“…Using a high-throughput approach combining acetylpeptide arrays with metabolomics analysis, Hallows et al identified ornithine transcarbamoylase (OTC) as a SIRT3 substrate (54). OTC is an enzyme that catalyzes the second step of the urea cycle, the key process in the detoxification of ammonia generated by amino-acid catabolism.…”
Section: Sirt3 Regulates the Urea Cycle Via Ornithine Transcarbamoylamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, SIRT3 is involved in fatty acid oxidation in the liver (Giralt and Villarroya, 2012). This was supported by evidence in SIRT3-knockout mice demonstrating increased palmitoylcarnitine and triacylglycerols in the liver and various acylcarnitines in the blood (Hallows et al, 2011;Hirschey et al, 2010). SIRT3 is also expressed abundantly in the heart, and its overexpression is protective against cardiac hypertrophy, while SIRT3 depletion enhances susceptibility to hypertrophy (Sundaresan et al, 2009).…”
Section: Sirt3mentioning
confidence: 90%
“…Here SIRT3 deacetylates and activates long-chain acylCoA dehydrogenase and medium-chain acyl-CoA dehydrogenase (MCAD) 3 (5,6). In parallel, under dietary restricted conditions, multiple fatty acid oxidation enzymes show increased lysine residue deacetylation in control versus SIRT3 knockout mice, and SIRT3 null mice have increased accumula-tion of acylcarnitines, a finding consistent with reduced fat oxidation (7). On the other hand, in response to fat feeding, the acetylation of ␤-hydroxyacyl CoA dehydrogenase results in activation of enzyme activity in muscle cells (8).…”
mentioning
confidence: 85%